Sectoral analysis of the impact of artificial intelligence on international trade in Turkey and the BRICS economies - Cüneyt, Çatuk (Springer Nature, 2025)
This study investigates how artificial intelligence (AI) adoption influences international trade performance across AI-intensive sectors in Turkey compared to the BRICS economies (Brazil, Russia, India, China, and South Africa) during the period 2019–2024. Using panel data regression models, the analysis quantifies AI’s effect on sectoral trade competitiveness, export–import dynamics, and macroeconomic stability. The findings reveal that AI investment significantly enhances trade efficiency, particularly in China and India, while high exchange rate volatility hampers trade performance in Turkey, Russia, and Brazil. AI infrastructure investment shows heterogeneous effects: it supports long-term trade growth but may limit short-term expansion due to high initial costs. Sectoral results indicate that China and India lead in AI-driven IT and FinTech exports, whereas Turkey demonstrates relative competitiveness in logistics and supply chain management but lags in broader digital transformation. Econometric analysis is conducted using random effects panel regression. This specification is justified through robustness checks in the absence of a feasible Hausman test due to multicollinearity in the fixed effects model. These findings provide statistically consistent insights into the role of AI in shaping trade performance across emerging economies. These results underscore the need for well-designed AI policies, targeted investments in industrial automation, and measures to ensure macroeconomic stability, enabling emerging economies like Turkey to maximize AI’s contribution to sustainable global trade growth. © The Author(s) 2025.
Keywords: Artificial intelligence (AI); BRICS economies; International trade; Random effects model; Sectoral trade analysis; Trade competitiveness